Comparing proxy and model estimates of hydroclimate variability and change over the Common Era - Smerdon, Jason E. (2017)
Water availability is fundamental to societies and ecosystems, but our understanding of variations 55 in hydroclimate (includingextreme events, flooding, and decadal periods of drought) is limited because of a paucity of modern instrumental observationsthat are distributed unevenly across the globe and only span parts of the 20th and 21st centuries. Such data coverage isinsufficient for characterizing hydroclimate and its associated dynamics because of its multidecadal-to-centennial variability andhighly regionalized spatial signature. High-resolution (seasonal to decadal) hydroclimatic proxies that span all or parts of the60 Common Era (CE) and paleoclimate model simulations are therefore important tools for augmenting our understanding ofhydroclimate variability. In particular, the comparison of the two sources of information is critical for addressing theuncertainties and limitations of both, while enriching each of their interpretations. We review the principal proxy data availablefor hydroclimatic reconstructions over the CE and highlight contemporary understanding of how these proxies are interpreted ashydroclimate indicators. We also review the available last-millennium simulations from fully-coupled climate models and65 discuss several outstanding challenges associated with simulating hydroclimate variability and change over the CE. A specificreview of simulated hydroclimatic changes forced by volcanic events is provided, as well as a discussion of expectedimprovements in estimated forcings, models and their implementation in the future. Our review of hydroclimatic proxies andlast-millennium model simulations is used as the basis for articulating a variety of considerations and best practices for how toperform proxy-model comparisons of CE hydroclimate. This discussion provides a framework for how best to evaluate70 hydroclimate variability and its associated dynamics using these comparisons, as well as how they can better informinterpretations of both proxy data and model simulations. We subsequently explore means of using proxy-model comparisonsto better constrain and characterize future hydroclimate risks. This is explored specifically in the context of several examplesthat demonstrate how proxy-model comparisons can be used to quantitatively constrain future hydroclimatic risks as estimatedfrom climate model projections.